EFEKTIVITAS PIJAT OKSITOSIN TERHADAP PENINGKATAN VOLUME ASI PADA IBU MENYUSUI DI KLINIK AS-SALAM - Yayuk Sri Rahayu; Euis Atikah; Ade Krisna Ginting; Riana Restu; Rizkika Naila (Jurnal Kesehatan dan Kedokteran, 2025)
Breastfeeding is the optimal source of nutrition for infants and plays an important role in supporting growth, development, and immunity. However, insufficient breast milk production remains a common problem among postpartum mothers and may affect the success of exclusive breastfeeding. Oxytocin massage has been widely used as a non-pharmacological intervention to stimulate oxytocin release and facilitate milk ejection. This study aimed to determine the effectiveness of oxytocin massage in increasing breast milk volume among breastfeeding mothers at As-salam Clinic. This study employed a quantitative approach using a quasi-experimental one-group pretest-posttest design. A total of 30 breastfeeding mothers participated in the study. Breast milk volume was measured before and after the administration of oxytocin massage. Data were analyzed using descriptive statistics and Paired Sample t-Test with a significance level of 0.05. The results showed that the mean breast milk volume increased from 41.9 ml before the intervention to 78.2 ml after the intervention. Statistical analysis revealed a significant difference in breast milk volume before and after oxytocin massage (p = 0.000). These findings indicate that oxytocin massage effectively improves breast milk volume among breastfeeding mothers. The study implies that oxytocin massage can be utilized as a simple, safe, and cost-effective intervention to support successful breastfeeding practices. The originality of this research lies in the direct measurement of breast milk volume using a pretest-posttest approach among breastfeeding mothers in a primary healthcare setting. The findings provide empirical evidence supporting the integration of oxytocin massage into maternal and child healthcare services.